THE EFFECTS OF SECONDARY MATHEMATICS COURSES ON RURAL STUDENT COLLEGE CHOICE - Howard, Susan Hope (East Carolina University, 2023)
Participation in a rigorous high school mathematics curriculum plays a key role in both college choice and college completion. Rural students have lower access to advanced mathematics courses and enroll in college at lower rates despite having a higher rate of high school completion than their non-rural peers. This dissertation utilizes the Hossler and Gallagher (1987) model of college choice and the High School Longitudinal Study of 2009 (HSLS:09) to further examine the relationship between rural high school mathematics and college choice. It was found that high school mathematics course work increased the probability of overall enrollment in college and of enrollment at a four-year institution. These results are important to higher educational leadership studies as they indicate the necessity for continued partnerships across the pipeline such as Math Pathways, The Launch Years, GEARUP, and Career and College Promise, which work to increase access to college for rural students.
Keywords: Mathematics--Study and teaching (Secondary); Rural schools; College choice; Educational leadership